Effects of Intra-Vitreal Diclofenac in Refractory Diabetic Macular Edema - Massana, Syed Hassan; Sadiq, Irfan; Sadiq, Usman; Zahra, Nida; Zafar, Sarah (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To see the effects of Intra-Vitreal Diclofenac injection (IVD) in refractory Diabetic Macular Edema (DME). Study Design: Quasi-experimental study. Place and Duration of Study: Retina Clinic, Al-Shifa Trust Eye Hospital, Rawalpindi Pakistan from Sep 2019 to Feb 2020. Methodology: Patients included in the study having Clinically Significant Macular Edema (CSME) with Central Macular Thickness (CMT) of more than 300 microns not responding to three consecutive Intravitreal injections of Bevacizumab (IVB).Intravitreal Diclofenac injection (500μg/0.1 ml) was given by the same retina fellow with the same protocol across all patients.Each patient was evaluated based on Central Macular Thickness (CMT) before intravitreal Diclofenac injection and on followup visits one week and one month after injection. Results: A total of 30 patients (30 eyes) were included in the study. Out of these, 11 were females, and 19 were males. The mean age of the patients was 57.87±4.424 years. Mean Central Macular Thickness (CMT) before injection was 439.67±110.45µm, after one week 398.47±110.55µm and 384.87±119.11µm after one month of intra-vitreal Diclofenac injection. Pre and post-injection central macular thickness (µm), which was clinically significant (p-value <0.001). Conclusion: Intravitreal Diclofenac injection (IVD) is effective in diabetic macular oedema, not responding to intravitreal antiVEGF (IVB) injections.